MUNICIPAL SOLID WASTE MANAGEMENT IN MALAYSIA - POSSIBILITY OF IMPROVEMENT? - S.H, Fauziah; C, Simon; P, Agamuthu (Malaysian Journal of Science, 2004)
Municipal Solid Waste (MSW) in Malaysia involves the disposal of approximately 98% of the total waste to landfills. Current disposal method of landfilling needs improvements to prolong the landfill life and to minimize the problem of land scarcity. Rapid developments and industrialization in Malaysia necessitate a better and more efficient waste management strategy. The mushrooming of urban areas and rural-urban migration has increased the per capita income due to changes in the consumption patterns that led to increased waste generation. The study involved the compilation of data from relevant municipalities on waste generation in Malaysia. The study also includes waste composition analysis according to income level, to determine the trends of composition produced. The local authorities and waste management consortia have to handle approximately 17,000 tonnes of MSW everyday throughout the country. MSW generation depends on the size of township and level of economical standard, that as low as 45 tonnes of MSW are generated in Kluang (a small town in the southern part of Peninsular Malaysia) to as high as 3000 tonnes in Kuala Lumpur (Malaysia’s capital). The largest sources are household waste followed by industrial and commercial waste. In Selangor state, the highest percentage of MSW consisted of putrescible waste of approximately 46%, followed by plastic and paper at 15% and 14%, respectively. The study indicated that composting can be incorporated in all the landfills in the country together with an integrated system of recycling. The integrated system would allow optimization of waste reduction and reuse programs, which is actually a realistic possibility to improve the MSW management in the country.